KATHRYN BULKOVAC’s STRUGGLES AGAINST WOMEN TRAFFICKING IN WHISTLEBLOWER MOVIE - WIDIATMOKO, ADHITYO HARIS (Jurnal Ilmiah Mahasiswa FIB, 2014)
Keywords: Patriarchy system, women trafficking, commodity of economyPatriarchy system basically is a social system in which men have higher levels of dominance than women. Similarly, the phenomenon of social system exists in Bosnia. Patriarchal system coupled with the chaos after the Balkan wars, has put this country in trouble trafficking of women. The number of Bosnians who are victims of war, especially men, resulting lost of social stability, both in the state and the family. A phenomenon which is also depicted in the film Whistleblower in which Bulkovac as the main character also struggle for women trafficking victims. To analyze this movie, the author uses the theory of feminism with a focus on how women are treated as an economic commodity.The results of this study show how the conditions of women trafficking victims from the point of view of Bulkovac as the main character. The victims here become economic commodity, shows how women snare to work, coupled with the dominance of patriarchy in Bosnia. Starting from the hopes of finding a better life, one of the key witnesses Bulkovac, joined the services of illegal labor brokers. The agencies have promised them to work as a waiter in a restaurant with high salaries. Without realizing it, a trap like this can pushed them down into the net that a lot of women trafficking in Bosnia as a country still ravaged. The victims, which has entered a country illegally causing them hesitate to seek legal counsel, especially due to their illegal status and also because many Bosnian police officers who took part in the woman trafficking. Furthermore, the victims must accept the fact that they are trapped in sexual commerciality, although it is not the victim's willingness. The conclusion, to be able to make up for their rights back, the victim must be willing to work for women trafficking of as sex labor. In this case Bulkovac as peacekeeper tasked to restore the social order was messed up due to the Balkan wars in Bosnia, as well as to help restore the rights of victims of trafficking of women who had taken away by the trafficker.